A hot melt prepreg with low-frequency wave absorbing performance and preparation and application thereof

CN121427252BActive Publication Date: 2026-10-09BEIJING COMPOSITE MATERIALS CO LTD +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511731567.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-10-09
Estimated Expiration
2045-11-24

AI Technical Summary

Technical Problem

CN119613920A公开了一种能促进吸波剂与树脂混合时的均匀性与相容性的高填充量吸波材料及零缺陷成型制备方法,该专利所用吸波剂为羰基铁粉或合金粉体,其填充量最高达到了90%,但吸波剂含量越多,越难以与树脂基体混合均匀,使得吸波剂与树脂混合时裹挟在树脂内部的空气越难脱除,在成型后材料内部会存在大量空洞缺陷

Benefits of technology

[0051] The hot-melt prepreg of the present invention with low-frequency microwave absorption performance adopts a sheet-like FeCoNi-based high-entropy alloy. By modifying the surface of the low-frequency microwave absorber, the uniformity and compatibility of the low-frequency microwave absorber in the resin matrix are effectively improved, thereby improving the microwave absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121427252B_ABST
    Figure CN121427252B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of hot melt prepreg with low-frequency wave-absorbing performance and its preparation and application, the prepreg includes wave-absorbing resin and fiber fabric;Wherein wave-absorbing resin component includes resin-coated wave-absorbing material, thermosetting resin and thermoplastic resin.The hot melt prepreg with low-frequency wave-absorbing performance of the present application realizes the low-frequency wave-absorbing performance of prepreg wideband high efficiency and good processing performance by optimizing the resin formula of wave-absorbing agent and prepreg preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microwave absorbing materials, and specifically relates to a hot-melt prepreg with low-frequency microwave absorbing properties, its preparation and application. Background Technology

[0002] With the iterative upgrading of modern defense technologies, radar detection systems are rapidly evolving towards lower frequencies and higher sensitivity. In particular, low-frequency radar systems (such as those in the UHF band, 0.3–3 GHz) are playing an increasingly important role in the modern military field. Due to their longer wavelengths, low-frequency radars can achieve over-the-horizon detection in ionospheric reflection mode, with a maximum effective range exceeding 3,000 kilometers. This makes over-the-horizon radar a core component of ballistic missile early warning systems. Simultaneously, this frequency band of electromagnetic waves has a significant penetration advantage through complex media such as jungles and sandstorms, and is widely used in ground-based mobile target reconnaissance systems.

[0003] In today's defense industry, aerospace and weaponry require not only excellent electromagnetic wave absorption performance but also high stability and load-bearing capacity to adapt to complex and ever-changing application environments. To address this need, research into structurally and functionally integrated electromagnetic wave absorbing composite materials is particularly important. These materials can not only effectively absorb electromagnetic waves and reduce reflections but also enhance structural stability through optimized structural design, thereby providing better stealth and load-bearing performance for equipment. Mixing fillers with low-frequency electromagnetic wave absorption properties (high-entropy alloys, iron-silicon-aluminum, ferrites, etc.) with a resin matrix to prepare low-frequency electromagnetic wave absorbing resins for use in fiber prepregs holds promise for obtaining structurally and functionally integrated composite materials. The hot-melt method, due to its advantages such as being solvent-free, allowing for controllable resin content, and producing prepregs with low porosity, has become one of the important processes for preparing prepregs. For microwave absorbing agent filling systems, the loss mechanism can only be enhanced when the filling amount is very high, and the microwave absorption performance of the prepreg can be significantly improved. In order to obtain hot melt prepreg with low-frequency broadband and high-efficiency microwave absorption performance, it is necessary to solve the technical problems (uniformity, compatibility, viscosity, preparation process) brought about by high filling amount of low-frequency microwave absorbing agent.

[0004] First, the uniformity of the high-filling-content absorbing agent in the resin and its compatibility with the resin matrix are key issues affecting the material's microwave absorption performance. Significant differences in physical properties exist between the absorbing agent and the resin matrix. Magnetic absorbing agents, due to their high magnetism and density, often tend to aggregate into clumps or settle, making it difficult to uniformly mix and stably bond with the resin matrix, thus hindering the achievement of low-frequency broadband and efficient microwave absorption performance. Existing patents mentioning the uniformity of the absorbing agent in the resin and its compatibility with the resin matrix disclose microwave absorbing films with high-filling-content cyano resin (CN117700784A) and their preparation methods, microwave absorbing films with high-filling-content polyimide resin (CN117659456A) and their preparation methods, and microwave absorbing films with high-filling-content epoxy resin (CN117624668A) and their preparation methods. The only difference between these three patents is the change of the resin. Patent CN117624668A involves coating the surface of a microwave absorbing agent (the absorbing agent is at least one selected from the group consisting of carbonyl iron, iron-silicon-aluminum, ferrite, conductive carbon black, carbon fiber, graphene, carbon nanotubes, and silicon carbide) with silica. The aim is to modify the original metallic chemical properties of the absorber into Si-OH chemical bonds. These chemical bonds can generate higher chemical activity with silane coupling agents, which is beneficial for subsequent silane coupling agent modification. After coating, the surface is modified with a silane coupling agent, which can transform the Si-OH chemical bonds on the surface of the absorber into a chemical structure with higher binding affinity to the resin. This chemical structure is beneficial for improving the interfacial bonding force between the absorber and the resin. This method allows the absorber filling amount in the resin to reach up to 85%, and the resulting prepreg exhibits good absorption performance in the 8–13 GHz range, with a reflection loss below -13 dB. CN119613920A discloses a high-filling-content microwave absorbing material and a zero-defect molding preparation method that can promote the uniformity and compatibility of the microwave absorbing agent and resin during mixing. The microwave absorbing agent used in this patent is carbonyl iron powder or alloy powder, and its filling content reaches up to 90%. However, the higher the content of the microwave absorbing agent, the more difficult it is to mix it evenly with the resin matrix. This makes it more difficult to remove the air trapped inside the resin when the microwave absorbing agent is mixed with the resin, resulting in a large number of voids and defects inside the material after molding. This patent addresses this problem using vibration and vacuum. A 90% filler absorbing slurry (composed of absorbers, binders, and various processing aids, also a mixture of absorbers and resin) is filled into a molding die. A three-dimensional vibration table is used to eliminate internal defects in the slurry, followed by a secondary defect elimination process in a vacuum oven, resulting in a zero-defect loaded absorbing material. The product was then sampled for material uniformity testing (a dispersion coefficient ≤10% is considered small). Materials using the invention method were defect-free with a dispersion coefficient of approximately 5%, while materials not using the invention method, in addition to defects, had a dispersion coefficient >10%, indicating poor uniformity.

[0005] The aforementioned patents did not address the low-frequency absorption performance of hot-melt prepregs when considering issues of uniformity and compatibility.

[0006] Secondly, the high-filling-content absorbing agent poses a significant challenge to the preparation process of hot-melt prepregs. As the filling content of low-frequency absorbing agents increases, the resin viscosity rises sharply, making the hot-melt prepreg difficult to process and mold. CN118744542A proposes a method for preparing low-frequency absorbing prepregs for the P and L bands. This method involves mixing a hot-melt thermosetting resin with an absorbing agent (one or more of FeSiAl alloy, FeSiCr alloy, or FeSiNi alloy), and combining this with the controlled parameters of a drum vulcanizing process to achieve the oriented alignment of the absorbing agent in the matrix. Compared to the uncalendered blank group, the optimal implementation improved the reflection loss at 1 GHz from -1.65 dB to -1.98 dB, at which point the filling content of the absorbing agent (sheet-like FeSiAl) was 33%. CN119431848A proposes an epoxy resin absorbing prepreg with strong low-frequency absorption performance and its preparation method. It utilizes a method of compounding sheet-like absorbers (at least one from the group consisting of carbonyl iron, iron-silicon-aluminum, and ferrite) with different particle sizes to increase the packing density of the absorbers within the absorbing prepreg, effectively improving the low-frequency electromagnetic loss of the absorbing prepreg. The absorbing prepreg is prepared by a thermal composite process of a magnetic absorbing film with a functional layer and a transparent fiber prepreg with a reinforcing layer. Optimal absorption performance is achieved when the absorbing agent (a 100 μm and 20 μm absorbing agent mixed in a 1:1 ratio) filler content is 60%, achieving a P-band reflection loss of -5.6 dB. In the aforementioned patent, whether it involves adding a calendering process or directly compounding the absorbing film with the transparent fiber prepreg, the aim is to solve the core problems caused by high filler content, such as high resin film viscosity making molding difficult, poor wettability with fibers, and weak interfacial bonding. Although the above process achieves good low-frequency absorption performance, it is not applicable when the absorber content exceeds 60%, making it difficult to meet the requirements for the low-frequency broadband and high-efficiency absorption performance of hot-melt prepregs. Furthermore, traditional methods of adding small-molecule toughening agents to thermosetting prepregs can significantly reduce resin viscosity and improve film-forming properties (e.g., patent CN103171225A mixes polyvinyl chloride powder with a toughening agent to form a prepreg, obtains a semi-finished product through padding and pre-drying, and then coats it with a polymer coating film; the toughening agent makes the film more flexible and easier to form; patent CN110951216A discloses a thermosetting resin composition and prepregs and laminates using it, proposing the addition of plasticizers such as triphenyl phosphate and isopropyltriphenyl phosphate (8-15 parts by weight) in an epoxy / phenolic resin system to improve the resin viscosity and film-forming properties). However, traditional plasticizers have low molecular weights and are prone to migration, leading to a decrease in the plasticizer content in the resin over time and a gradual loss of plasticizing effect. At the same time, the plasticizers that migrate out can also contaminate the contact objects and the environment. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a hot melt prepreg with low frequency (0.3~3 GHz) wave absorption performance and its preparation and application.

[0008] The present invention provides a microwave absorbing resin, which, by weight percentage, comprises 50-80 wt% resin-coated microwave absorbing material (A), 15-45 wt% thermosetting resin (B), and 5-15 wt% thermoplastic resin (C).

[0009] Preferably, the resin-coated microwave absorbing material is a microwave absorbing agent with a surface treatment of thermoplastic resin coated with a silane coupling agent;

[0010] The absorber is a low-frequency absorber, wherein the low-frequency absorbing agent is an FeCoNi-based high-entropy alloy, and the absorbing agent is in the form of flakes with a size of 1~100 μm;

[0011] The FeCoNi-based high-entropy alloy includes one or more of FeCoNiAlCr, FeCoNiCrCu, and FeCoNiCuAl.

[0012] The curing temperature of the thermosetting resin is room temperature to 400 ℃.

[0013] Preferably, the thermosetting resin is selected from one or more of the following: epoxy resin (typical curing temperature is room temperature to 120 ℃, low temperature curing resin), phenolic resin (typical curing temperature is 150 to 180 ℃, medium temperature curing resin), cyanate ester resin (typical curing temperature is 160 to 220 ℃, medium temperature curing resin), bismaleimide resin (typical curing temperature is 180 to 250 ℃, high temperature curing resin), and polyimide resin (typical curing temperature is 300 to 400 ℃, high temperature curing resin).

[0014] Preferably, the thermoplastic resin includes one or more of polyethersulfone, polyphenylene sulfide, polyetherimide, polyoxymethylene, polybutylene terephthalate, polycarbonate, and polyvinyl alcohol.

[0015] Preferably, the thermoplastic resin used in the resin-coated microwave absorbing material (A) is the same as that used in the thermoplastic resin (C).

[0016] This invention provides a method for preparing microwave absorbing resin, comprising: mixing thermosetting resin and thermoplastic resin, then adding resin-coated microwave absorbing material and kneading, grinding, to obtain microwave absorbing resin.

[0017] The present invention provides a microwave absorbing prepreg, the prepreg comprising microwave absorbing resin and fiber fabric; wherein the fiber fabric is disposed between the microwave absorbing resin.

[0018] The fiber fabric is a low dielectric loss fiber fabric.

[0019] Preferably, the fiber fabric comprises one or more of glass fiber, quartz fiber, aramid fiber, basalt fiber, polyimide fiber, and silicon carbide fiber, with an areal density of 100~800 g / m³. 2 .

[0020] This invention provides a method for preparing a microwave absorbing prepreg, comprising:

[0021] (1) Preparation of microwave absorbing resin:

[0022] Thermosetting resin and thermoplastic resin are mixed evenly, and then resin-coated microwave absorbing material is added, kneaded, and ground to obtain microwave absorbing resin.

[0023] (2) Preparation of hot-melt prepreg:

[0024] The microwave absorbing resin is made into a microwave absorbing film, and then the fiber fabric is placed between the microwave absorbing film for lamination. After post-treatment, a microwave absorbing prepreg is obtained.

[0025] The preferred embodiment of the above preparation method is as follows:

[0026] The preparation of the resin-coated microwave absorbing material in step (1) includes: dispersing a silane coupling agent in a mixed solution of ethanol and water, adding a microwave absorbing agent and ultrasonically oscillating to obtain a surface-treated microwave absorbing agent; then mixing the resin solution and the surface-treated microwave absorbing agent and reacting to obtain the resin-coated microwave absorbing material.

[0027] The silane coupling agent includes one or more of KH550, KH560, KH570, and KH792; the resin is a thermoplastic resin, wherein the thermoplastic resin includes one or more of polyethersulfone, polyphenylene sulfide, polyetherimide, polyoxymethylene, polybutylene terephthalate, polycarbonate, and polyvinyl alcohol.

[0028] The silane coupling agent is dispersed in a mixed solution of ethanol and water and stirred for 10-30 minutes.

[0029] The ultrasonic oscillation treatment time is 10~50 min; the reaction temperature is 55~65 ℃, and the time is 6~7 h;

[0030] After ultrasonic oscillation treatment, the surface-treated microwave absorber is obtained by centrifugation, filtration, washing, and drying; the centrifugation speed is 3000~5000 r / min, the time is 5~15 min; the drying is vacuum drying, the temperature is 60~80 °C, and the time is 6~8 h.

[0031] The amount of silane coupling agent used is 0.5~2wt% of the microwave absorber;

[0032] The resin solution is prepared by dissolving the resin in a solvent and then ultrasonically dispersing it for 30-60 minutes.

[0033] The solvent of the resin solution includes one or more of acetone, N-methylpyrrolidone, and dimethyl sulfoxide;

[0034] The amount of resin used is 5-10 wt% of the microwave absorber.

[0035] After the reaction, a suspension was obtained, which was then centrifuged, filtered, dried, and ground into powder to obtain a dry powder of the resin-coated microwave absorbing material. The centrifugation speed was 3000~5000 r / min, and the time was 5~15 min; the drying was carried out under vacuum at a temperature of 60~80 °C for 6~8 h.

[0036] In step (1), the compound system of thermosetting resin and thermoplastic resin is used as the matrix resin.

[0037] In step (1), the mixing is a intensive mixing process, with a temperature of 80~200℃ and a rotation speed of 50~150 r / min.

[0038] In step (1), the mixing time is 20-100 min at 80-200 ℃.

[0039] Furthermore, the mixing process is controlled in two stages: in the early stage, the temperature is controlled at 110~200℃ and the mixing time is 10~60 min; in the later stage, the temperature is controlled at 60~100℃ and the mixing time is 10~20 min.

[0040] In step (1), the grinding is a three-roll grinding process, with a gap of 10~100 μm between the rollers, a roller temperature of 60~100℃, and grinding 3~5 times.

[0041] In step (2), the microwave absorbing resin is used to make the microwave absorbing film by calendering.

[0042] The rolling temperature is 60~100 °C, the rolling thickness is 0.05~0.2 mm, the rolling pressure is 5~50 MPa, and the rolling speed is 0.5~5 m / s.

[0043] The step (2) of laminating the fiber fabric between the microwave absorbing film includes: drawing the microwave absorbing film out from the upper and lower film rollers of the prepreg machine and performing double-film sandwich thermal lamination with the fiber fabric, and fixing the distance between each roller; wherein the distance between each roller of the prepreg machine is 0.3~0.5 mm, the temperature of the heating roller is 60~200 ℃, and the fiber impregnation rate is 0.3~5 m / min.

[0044] The post-processing in step (2) includes cooling to room temperature and winding.

[0045] Further, the microwave absorbing film is drawn out from the upper and lower film rollers of the prepreg machine and thermally laminated with low dielectric loss fiber fabric in a double-film sandwich configuration. The distance between each roller is fixed so that the matrix resin can fully impregnate the fiber fabric. The temperature of the prepreg is rapidly reduced to room temperature using a cooling plate, and the prepreg is then wound up to obtain the prepreg.

[0046] This invention provides an application of any of the aforementioned radar-absorbing prepregs in the fields of radar, aerospace, and weaponry. For example, its application in broadband, high-performance stealth and protection structures for low-frequency skywave over-the-horizon radar and ground reconnaissance radar.

[0047] This invention focuses on overcoming the bottlenecks in the preparation process of low-frequency absorbing resins and their hot-melt prepregs caused by high filler content of low-frequency absorbing agents. Its innovation lies not only in addressing the compatibility between the low-frequency absorbing agent and the resin matrix, but also in effectively solving the process problems caused by the significant increase in viscosity at high filler content. Furthermore, this invention employs a FeCoNi-based high-entropy alloy as a low-frequency absorbing agent and provides customized prepreg preparation process optimization for hot-melt prepregs with low-frequency absorbing properties, including but not limited to: surface modification of the low-frequency absorbing agent (resin coating of the low-frequency absorbing agent), regulation of the rheological behavior of the absorbing resin (optimization of resin formulation), and optimization of the prepreg molding process (adaptation design of physical mixing technology and hot-melt prepreg process parameters). The resin-coated absorbing agent structure effectively alleviates particle agglomeration and improves the interfacial compatibility between the absorbing agent and the resin matrix. The coating resin and the matrix resin are the same, allowing for minimal control of the material composition by adjusting the filler content of the low-frequency absorbing agent and the resin curing parameters. This resin-coated low-frequency absorbing agent structure effectively avoids impedance mismatch problems caused by the introduction of heterogeneous materials while ensuring strong interfacial bonding (e.g., in patent CN117659456A, the absorber is coated with silica, and the introduction of silica makes the already complex composition of the prepreg (absorbing agent, resin, fiber) even more complex. Silica as a coating layer changes the local electromagnetic field distribution around the absorber, and this change is particularly sensitive at low frequencies. The coating thickness affects interfacial bonding and loss performance, making it much more difficult to control the low-frequency broadband high-efficiency absorbing performance). This invention, while ensuring excellent compatibility, successfully reduces melt viscosity by precisely controlling rheological behavior through the blending of thermosetting and thermoplastic resins. Even at high filler contents, the low-frequency absorbing resin and its hot-melt prepreg maintain excellent processing performance. This patent, while ensuring good processing performance, adjusts the process parameters of hot melt prepreg, selecting appropriate temperature, pressure, impregnation rate, etc., and combining physical mixing technology (internal mixer, three-roll mill, calendering, etc.) to finally achieve full impregnation of the fiber by the microwave absorbing resin, thereby comprehensively improving the microwave absorption performance, mechanical properties and processing performance of the low frequency microwave absorbing prepreg.

[0048] The synergistic control system of "resin-coated low-frequency absorbing agent - resin rheology regulation - process parameter optimization" constructed in this invention provides a new experimental basis and technical path for realizing the structural / functional integration of microwave absorbing composite materials.

[0049] The low-frequency absorbing agent of this invention, as an electromagnetic functional filler, exhibits outstanding performance in achieving low-frequency absorption properties when combined with a resin matrix.

[0050] Beneficial effects

[0051] The hot-melt prepreg of the present invention with low-frequency microwave absorption performance adopts a sheet-like FeCoNi-based high-entropy alloy. By modifying the surface of the low-frequency microwave absorber, the uniformity and compatibility of the low-frequency microwave absorber in the resin matrix are effectively improved, thereby improving the microwave absorption performance.

[0052] The hot-melt prepreg of the present invention with low-frequency microwave absorption properties adjusts the rheological properties by compounding thermosetting resin and thermoplastic resin, improves the viscosity problem of high-filler resin, and improves the wettability and spreadability of the prepreg, so as to meet the requirements of composite material molding process.

[0053] The hot-melt prepreg of the present invention, which has low-frequency microwave absorption properties, achieves broadband and efficient low-frequency microwave absorption and processing performance by optimizing the resin formulation of the microwave absorber and the prepreg preparation process. Attached Figure Description

[0054] Figure 1 This describes the preparation process of hot-melt prepreg with low-frequency microwave absorption properties. Detailed Implementation

[0055] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0056] Unless otherwise specified in the specific embodiments of this invention, the conditions shall be performed according to conventional conditions or the manufacturer's recommendations. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0057] In the following implementation examples, component A represents a low-frequency absorbing agent, which is FeCoNiCrCu in the implementation examples; component B represents a thermosetting resin, which includes epoxy resin, phenolic resin, and cyanate ester resin in the implementation examples; and component C represents a thermoplastic resin, which includes polyethersulfone and polyphenylene sulfide in the implementation examples.

[0058] In Examples 1-4 and Comparative Examples 1 and 3, the amount of silane coupling agent used was 1 wt% of the microwave absorber.

[0059] Example 1

[0060] Low-frequency microwave absorbing hot-melt prepreg was prepared using the following method:

[0061] (1) Polyethersulfone (5 wt% of the microwave absorber) was dissolved in N-methylpyrrolidone and ultrasonically dispersed for 30 min to obtain a polyethersulfone solution. The surface of sheet-like FeCoNiCrCu with an average size of 50 μm was treated with silane coupling agent KH550. The treatment method was to disperse silane coupling agent KH550 in a mixed solution of ethanol and water and stir for 30 min. Then, low-frequency microwave absorber was added and ultrasonically oscillated for 30 min. After centrifugation, filtration, washing, and drying, the surface-treated low-frequency microwave absorber was obtained. Then, the surface-treated low-frequency microwave absorber was added to the polyethersulfone solution and the mixture was heated and stirred at 60 °C for 6-7 h to obtain a suspension. After centrifugation, filtration, and drying, resin-coated microwave absorber (A) was obtained. The centrifugation speed was 3000~5000 r / min and the time was 5~15 min. The drying was vacuum drying at a temperature of 60~80 °C and a time of 6~8 h.

[0062] (2) A low-temperature curing epoxy resin (B) and polyethersulfone (C) composite system was selected as the matrix resin. The matrix resin was mixed evenly in a mixer at 120 °C with a rotor speed of 50 r / min. Then, A was added and mixed in two stages for 60 min. The weight ratio of A, B, and C was 70 wt%, 23 wt%, and 7 wt%. The mixing temperature was controlled in two stages: 120 °C for 50 min in the first stage and 80 °C for 10 min in the second stage. The mixture was then ground by three rollers (10 μm gap between rollers, 80 °C roller temperature, 3-5 times) to obtain the microwave absorbing resin.

[0063] (3) The prepared microwave absorbing resin is calendered into a microwave absorbing film at a calendering temperature of 80 °C, a calendering thickness of 0.1 mm, a calendering pressure of 30 MPa, and a calendering speed of 3 m / s. The microwave absorbing film is then drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with glass fibers in a double-film sandwich configuration. The fiber surface density is 600 g / m². 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 60 ℃, and the fiber impregnation rate is 2 m / min.

[0064] Example 2

[0065] Example 2: Low-frequency microwave absorbing hot-melt prepreg was prepared by the following method (the difference from Example 1 is that the thermosetting / thermoplastic resin compound system used is epoxy resin / polyphenylene sulfide):

[0066] 1) Polyphenylene sulfide (PPS) accounting for 5 wt% of the microwave absorber was dissolved in dimethyl sulfoxide (DMSO) and ultrasonically dispersed for 30 min to obtain a PPS solution. The surface of 50 μm sheet-like FeCoNiCrCu particles was treated with a silane coupling agent KH550. The treatment method involved dispersing the silane coupling agent KH550 in a mixed solution of ethanol and water and stirring for 30 min. Then, the low-frequency microwave absorber was added, and the mixture was ultrasonically vibrated for 30 min. After centrifugation, filtration, washing, and drying, the surface-treated low-frequency microwave absorber was obtained. The surface-treated low-frequency microwave absorber was then added to a DMSO solution, and the mixture was heated and stirred at 60 °C for 6–7 h to obtain a suspension. This suspension was then centrifuged, filtered, and dried to obtain the resin-coated microwave absorber (A). Centrifugation speed was 3000–5000 r / min for 5–15 min; drying was performed under vacuum at 60–80 °C for 6–8 h.

[0067] 2) A low-temperature curing epoxy resin (B) and polyphenylene sulfide (C) composite system was selected as the matrix resin. The matrix resin was mixed evenly in a Banbury mixer at 160 °C with a rotor speed of 100 r / min. Then, resin A was added and mixed in two stages for 60 min. The weight ratio of A, B, and C was 70 wt%, 21 wt%, and 9 wt%, respectively. The mixing temperature was controlled in two stages: the initial temperature was 160 °C for 50 min, and the subsequent temperature was 80 °C for 10 min. The mixture was then ground using a three-roll mill (roller gap 25 μm, roller temperature 80 °C, milling 3-5 times) to obtain the microwave absorbing resin.

[0068] 3) The prepared microwave-absorbing resin is calendered into an absorbing film using a calendering process. The calendering temperature is 80 °C, the calendering thickness is 0.1 mm, the calendering pressure is 20 MPa, and the calendering speed is 3 m / s. Then, the absorbing film is drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with glass fibers in a double-film sandwich configuration. The fiber areal density is 600 g / m². 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 70 ℃, and the fiber impregnation rate is 1 m / min.

[0069] Example 3

[0070] Example 3 describes the preparation of a low-frequency microwave absorbing hot-melt prepreg using the following method (the difference from Example 1 is that the thermosetting / thermoplastic resin compound system used is cyanate ester / polyethersulfone):

[0071] 1) Polyethersulfone (5 wt% of the microwave absorber) was dissolved in N-methylpyrrolidone and ultrasonically dispersed for 30 min to obtain a polyethersulfone solution. The surface of 50 μm flake-shaped FeCoNiCrCu sheets was treated with a silane coupling agent KH550. The treatment method involved dispersing the silane coupling agent KH550 in a mixed solution of ethanol and water and stirring for 30 min. Then, the low-frequency microwave absorber was added, and the mixture was ultrasonically vibrated for 30 min. After centrifugation, filtration, washing, and drying, the surface-treated low-frequency microwave absorber was obtained. The surface-treated low-frequency microwave absorber was then added to the polyethersulfone solution, and the mixture was heated and stirred at 60 °C for 6–7 h to obtain a suspension. This suspension was then centrifuged, filtered, and dried to obtain the resin-coated microwave absorber (A). Centrifugation speed was 3000–5000 r / min for 5–15 min; drying was performed under vacuum at 60–80 °C for 6–8 h.

[0072] 2) A medium-temperature curing resin mixture of cyanate ester resin (B) and polyethersulfone (C) was selected as the matrix resin. The matrix resin was mixed uniformly in a Banbury mixer at 180 °C with a rotor speed of 150 r / min. Then, resin A was added and mixed in two stages for 60 min. The weight ratio of A, B, and C was 70 wt%, 18 wt%, and 12 wt%, respectively. The mixing temperature was controlled in two stages: the initial temperature was 180 °C for 50 min, and the subsequent temperature was 90 °C for 10 min. The mixture was then ground using a three-roll mill (roller gap 50 μm, roller temperature 90 °C, milling 3-5 times) to obtain the microwave absorbing resin.

[0073] 3) The prepared microwave-absorbing resin is calendered into an absorbing film using a calendering process. The calendering temperature is 80 °C, the calendering thickness is 0.1 mm, the calendering pressure is 10 MPa, and the calendering speed is 3 m / s. Then, the absorbing film is drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with glass fibers in a double-film sandwich configuration. The fiber surface density is 600 g / m³. 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 90 ℃, and the fiber impregnation rate is 0.5 m / min.

[0074] Example 4

[0075] Example 4: Low-frequency microwave absorbing hot-melt prepreg was prepared using the following method (the difference from Example 1 is that the fiber fabric used is basalt fiber):

[0076] 1) Polyethersulfone (5 wt% of the microwave absorber) was dissolved in N-methylpyrrolidone and ultrasonically dispersed for 30 min to obtain a polyethersulfone solution. The surface of 50 μm flake-shaped FeCoNiCrCu sheets was treated with a silane coupling agent KH550. The treatment method involved dispersing the silane coupling agent KH550 in a mixed solution of ethanol and water and stirring for 30 min. Then, the low-frequency microwave absorber was added, and the mixture was ultrasonically vibrated for 30 min. After centrifugation, filtration, washing, and drying, the surface-treated low-frequency microwave absorber was obtained. The surface-treated low-frequency microwave absorber was then added to the polyethersulfone solution, and the mixture was heated and stirred at 60 °C for 6–7 h to obtain a suspension. This suspension was then centrifuged, filtered, and dried to obtain the resin-coated microwave absorber (A). Centrifugation speed was 3000–5000 r / min for 5–15 min; drying was performed under vacuum at 60–80 °C for 6–8 h.

[0077] 2) A low-temperature curing epoxy resin (B) and polyethersulfone (C) composite system was selected as the matrix resin. The matrix resin was mixed evenly in a Banbury mixer at 120 °C with a rotor speed of 50 r / min. Then, resin A was added and mixed in two stages for 60 min. The weight ratio of A, B, and C was 70 wt%, 23 wt%, and 7 wt%, respectively. The mixing temperature was controlled in two stages: the initial temperature was 120 °C for 50 min, and the subsequent temperature was 80 °C for 10 min. The mixture was then ground using a three-roll mill (10 μm gap between rollers, 80 °C roller temperature, 3-5 milling cycles) to obtain the microwave absorbing resin.

[0078] 3) The prepared microwave-absorbing resin is calendered into a microwave-absorbing film using a calendering process. The calendering temperature is 80 °C, the calendering thickness is 0.1 mm, the calendering pressure is 30 MPa, and the calendering speed is 3 m / s. Then, the microwave-absorbing film is drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with basalt fibers in a double-film sandwich structure. The fiber areal density is 600 g / m³. 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 60 ℃, and the fiber impregnation rate is 2 m / min.

[0079] Comparative Example 1

[0080] Comparative Example 1 (different from Example 1 in that the amount of low-frequency absorbing agent used is 50%) was prepared by the following method:

[0081] 1) Polyethersulfone (5 wt% of the microwave absorber) was dissolved in N-methylpyrrolidone and ultrasonically dispersed for 30 min to obtain a polyethersulfone solution. The surface of 50 μm flake-shaped FeCoNiCrCu sheets was treated with a silane coupling agent KH550. The treatment method involved dispersing the silane coupling agent KH550 in a mixed solution of ethanol and water and stirring for 30 min. Then, the low-frequency microwave absorber was added, and the mixture was ultrasonically vibrated for 30 min. After centrifugation, filtration, washing, and drying, the surface-treated low-frequency microwave absorber was obtained. The surface-treated low-frequency microwave absorber was then added to the polyethersulfone solution, and the mixture was heated and stirred at 60 °C for 6–7 h to obtain a suspension. This suspension was then centrifuged, filtered, and dried to obtain the resin-coated microwave absorber (A). Centrifugation was performed at 3000–5000 r / min for 5–15 min; drying was performed under vacuum at 60–80 °C for 6–8 h.

[0082] 2) A low-temperature curing epoxy resin (B) and polyethersulfone (C) composite system was selected as the matrix resin. The matrix resin was mixed evenly in a Banbury mixer at 120 °C with a rotor speed of 50 r / min. Then, resin A was added and mixed in two stages for 60 min. The weight ratio of A, B, and C was 50 wt%, 15 wt%, and 35 wt%. The mixing temperature was controlled in two stages: the initial temperature was 120 °C for 50 min, and the subsequent temperature was 80 °C for 10 min. The mixture was then ground using a three-roll mill (10 μm gap between rollers, 80 °C roller temperature, 3-5 milling cycles) to obtain the microwave absorbing resin.

[0083] 3) The prepared microwave-absorbing resin is calendered into a microwave-absorbing film at a calendering temperature of 80 °C, a calendering thickness of 0.1 mm, a calendering pressure of 30 MPa, and a calendering speed of 3 m / s. The microwave-absorbing film is then drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with glass fibers in a double-film sandwich configuration. The fiber surface density is 600 g / m³. 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 60 ℃, and the fiber impregnation rate is 2 m / min.

[0084] Comparative Example 2

[0085] Comparative Example 2, a low-frequency microwave absorbing hot-melt prepreg, was prepared using the following method (the difference from Example 1 is that the step of coating the low-frequency microwave absorbing agent with thermoplastic resin was not performed):

[0086] 1) A low-temperature curing epoxy resin (B) and polyethersulfone (C) composite system was selected as the matrix resin. The matrix resin was mixed evenly in a Banbury mixer at 120 °C with a rotor speed of 50 r / min. Then, 50 μm flake-shaped FeCoNiCrCu low-frequency absorbing agent without thermoplastic resin coating was added and mixed in two stages for 60 min. The weight ratio of low-frequency absorbing agent, B, and C was 70 wt%, 23 wt%, and 7 wt%. The mixing temperature was controlled in two stages: the initial temperature was 120 °C for 50 min, and the subsequent temperature was 80 °C for 10 min. The mixture was then ground using a three-roll mill (10 μm gap between rollers, 80 °C roller temperature, 3-5 milling cycles) to obtain the absorbing resin.

[0087] 2) The prepared microwave-absorbing resin is calendered into an absorbing film using a calendering process. The calendering temperature is 80 °C, the calendering thickness is 0.1 mm, the calendering pressure is 30 MPa, and the calendering speed is 3 m / s. Then, the absorbing film is drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with glass fibers in a double-film sandwich configuration. The fiber surface density is 600 g / m³. 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 60 ℃, and the fiber impregnation rate is 2 m / min.

[0088] Comparative Example 3

[0089] Comparative Example 3, a low-frequency microwave absorbing hot melt prepreg, was prepared by the following method (the difference from Example 1 is that the mixing temperature was not controlled in two stages):

[0090] (1) Polyethersulfone (5 wt% of the microwave absorber) was dissolved in N-methylpyrrolidone and ultrasonically dispersed for 30 min to obtain a polyethersulfone solution. The surface of sheet-like FeCoNiCrCu with an average size of 50 μm was treated with silane coupling agent KH550. The treatment method was to disperse silane coupling agent KH550 in a mixed solution of ethanol and water and stir for 30 min. Then, low-frequency microwave absorber was added and ultrasonically oscillated for 30 min. After centrifugation, filtration, washing, and drying, the surface-treated low-frequency microwave absorber was obtained. Then, the surface-treated low-frequency microwave absorber was added to the polyethersulfone solution and the mixture was heated and stirred at 60 °C for 6-7 h to obtain a suspension. After centrifugation, filtration, and drying, resin-coated microwave absorber (A) was obtained. The centrifugation speed was 3000~5000 r / min and the time was 5~15 min. The drying was vacuum drying at a temperature of 60~80 °C and a time of 6~8 h.

[0091] (2) A low-temperature curing epoxy resin (B) and polyethersulfone (C) composite system was selected as the matrix resin. The matrix resin was mixed evenly in a mixer at 120 °C with a rotor speed of 50 r / min. Then, A was added and mixed for 60 min. The weight ratio of A, B, and C was 70 wt%, 23 wt%, and 7 wt%. The mixing temperature was 120 °C. The mixture was then ground by three rollers (10 μm gap between rollers, roller temperature 80 °C, grinding 3-5 times) to obtain the microwave absorbing resin.

[0092] (3) The prepared microwave absorbing resin is calendered into a microwave absorbing film at a calendering temperature of 80 °C, a calendering thickness of 0.1 mm, a calendering pressure of 30 MPa, and a calendering speed of 3 m / s. The microwave absorbing film is then drawn out from the upper and lower film rollers of a prepreg machine and thermally laminated with glass fibers in a double-film sandwich configuration. The fiber surface density is 600 g / m². 2 The spacing between the rollers is fixed to allow the matrix resin to fully impregnate the glass fiber cloth. A cooling plate is used to rapidly lower the temperature of the prepreg to room temperature, and the prepreg is then wound up to obtain the final product. The roller spacing is 0.3 mm, the temperature of the heating roller is 60 ℃, and the fiber impregnation rate is 2 m / min.

[0093] For the hot melt prepregs with low-frequency microwave absorption properties obtained in Examples 1-4 and Comparative Examples 1-3 above, their microwave absorption performance and process performance were tested at room temperature. The test results are shown in Table 1.

[0094] Table 1. Microwave absorption properties and wettability of hot-melt prepregs with low-frequency microwave absorption properties

[0095]

[0096] The absorption performance test used in the experiment was conducted in accordance with the GB / T 38118-2019 standard. The main equipment and parameters were as follows: Vector network analyzer (model: ZNB 20): frequency range: 0.1-8 GHz, reflectivity test dynamic range: -60 dB to 0 dB, test sample size: inner diameter of circular test piece 3.04 mm, outer diameter 7.0 mm; square test piece 180 mm × 180 mm × 2 mm.

[0097] The wettability test of the prepreg used in the experiment was conducted according to the enterprise standard (Q / ABC 2023-01). The main equipment and parameters were: contact angle measuring instrument (model: Dataphysics OCA50) with a measurement resolution of 0.1°, resin drop volume of 5±0.5 μL, and fiber substrate temperature of 60±2 ℃. Wetting grade determination: Grade I (θ<10°): complete wetting; Grade II (10°≤θ<30°): good wetting; Grade III (θ≥30°): process optimization is required.

Claims

1. A microwave absorbing resin, characterized in that, By weight percentage, the microwave absorbing resin comprises 70-80 wt% resin-coated microwave absorbing material, 15-23 wt% thermosetting resin, and 5-15 wt% thermoplastic resin; The microwave absorbing resin is prepared by the following method: thermosetting resin and thermoplastic resin are mixed evenly, then resin-coated microwave absorbing material is added and kneaded, and ground to obtain microwave absorbing resin; the mixing is intensive mixing, the temperature is 80~200 ℃, and the rotation speed is 50~150 r / min. The mixing time is 20-100 min at 80-200 ℃; The grinding is a three-roll grinding process, with a roller gap of 10~100 μm, a roller temperature of 60~100 ℃, and grinding 3~5 times; The mixing process is controlled in two stages: the initial temperature is controlled at 110~200℃ and the mixing time is 10~60 min; the later temperature is controlled at 60~100℃ and the mixing time is 10~20 min. The resin-coated microwave absorbing material is a microwave absorbing agent with a surface treatment of thermoplastic resin coated with silane coupling agent; The microwave absorber is a FeCoNi-based high-entropy alloy, and the microwave absorber is in the form of flakes with a size of 1~100 μm; The FeCoNi-based high-entropy alloy includes one or more of FeCoNiAlCr, FeCoNiCrCu, and FeCoNiCuAl; The thermosetting resin includes one or more of epoxy resin, phenolic resin, cyanate ester resin, bismaleimide resin, and polyimide resin; the thermoplastic resin includes one or more of polyethersulfone, polyphenylene sulfide, polyetherimide, polyoxymethylene, polybutylene terephthalate, polycarbonate, and polyvinyl alcohol.

2. A microwave-absorbing prepreg, characterized in that, The prepreg comprises the microwave absorbing resin of claim 1 and the fiber fabric; wherein the fiber fabric is disposed between the microwave absorbing resins.

3. A method for preparing the microwave absorbing prepreg as described in claim 2, comprising: (1) Mix the thermosetting resin and thermoplastic resin evenly, then add the resin-coated microwave absorbing material, knead and grind to obtain microwave absorbing resin; The mixing in step (1) is intensive mixing, with a temperature of 80~200 ℃ and a rotation speed of 50~150 r / min; In step (1), the mixing time is 20-100 min at 80-200 ℃; In step (1), the grinding is a three-roll grinding, with a gap between the rollers of 10~100 μm, a roller temperature of 60~100 ℃, and grinding 3~5 times; the mixing is controlled in two stages, with the temperature controlled at 110~200℃ in the early stage and the mixing time being 10~60 min, and the temperature controlled at 60~100 ℃ in the later stage and the mixing time being 10~20 min. (2) The microwave absorbing resin is made into a microwave absorbing film, and then the fiber fabric is placed between the microwave absorbing film for composite, followed by post-treatment to obtain microwave absorbing prepreg.

4. The preparation method according to claim 3, characterized in that, The preparation of the resin-coated microwave absorbing material in step (1) includes: dispersing a silane coupling agent in a mixed solution of ethanol and water, adding a microwave absorbing agent and ultrasonically oscillating to obtain a surface-treated microwave absorbing agent; then mixing the resin solution and the surface-treated microwave absorbing agent and reacting to obtain the resin-coated microwave absorbing material.

5. The preparation method according to claim 4, characterized in that, The silane coupling agent includes one or more of KH550, KH560, KH570, and KH792; The ultrasonic oscillation treatment time is 10-50 min; the reaction temperature is 55-65 ℃, and the time is 6-7 h.

6. The preparation method according to claim 3, characterized in that, In step (2), the microwave absorbing resin is made into a microwave absorbing film by calendering process; wherein the calendering temperature is 60~100 °C, the calendering thickness is 0.05~0.2 mm, the calendering pressure is 5~50 MPa, and the calendering speed is 0.5~5 m / s. The step (2) of laminating the fiber fabric between the microwave absorbing membranes includes: drawing the microwave absorbing membrane out from the upper and lower membrane rollers of the prepreg machine and performing double-membrane sandwich thermal lamination with the fiber fabric; wherein the distance between each roller of the prepreg machine is 0.3~0.5 mm, the temperature of the heating roller is 60~200 ℃, and the fiber impregnation rate is 0.3~5 m / min; The post-processing in step (2) includes cooling to room temperature and winding.

7. The application of the microwave absorbing prepreg of claim 2 in the fields of radar, aerospace, and weaponry.

Citation Information

Patent Citations

  • Preparation method of energy-storing and color-variable building film material

    CN103171225A

  • Epoxy resin wave-absorbing adhesive film with high strength and high filling amount and preparation method of epoxy resin wave-absorbing adhesive film

    CN117624668A

  • High-strength high-filling-amount polyimide resin wave-absorbing adhesive film and preparation method thereof

    CN117659456A

  • High-strength high-filling-amount cyano resin wave-absorbing adhesive film and preparation method thereof

    CN117700784A

  • Preparation method of low-frequency wave-absorbing prepreg for P and L wave bands

    CN118744542A